Modelling of surface wind in petuniabukta (Billefjorden, Svalbard) - Chládová, Z. (Zuzana); Láska, K.; Hošek, J. (Jiří) (2014)
Atmospheric boundary layer processes in Arctic fjords are strongly influenced by complex topography. The topographic effects may include channelling, drainage flows and mountain waves in particular (Láska et al. 2012). Modelling of these effects in the case of small-scale topography requires very high resolution of both wind measurements and suitable tool for parameterisation of the atmospheric boundary layer. There are only few studies which deal with comparison of the observed and estimated wind conditions in the Arctic summer. In this study, the numerical simulation by means of the Weather Research Forecasting (WRF) model (Skamarock et al. 2007) and WAsP Engineering model (Troen and Petersen, 1989) were used. The WRF model can catch a large spatial variation in near-surface variables over fjords. The simulations have previously been evaluated against measurement of the weather stations on Greenland, Svalbard and Arctic Ocean in spring and the results were satisfactory. WAsP Engineering model supports mainly the estimation of loads on wind turbines and other civil engineering structures situated in moderately complex terrain.